54‐1: Invited Paper: AR in an Automobile: 3D AR‐HUD. Issue 1 (28th June 2022) - Jeong, Eunyoung; Jeon, Junho; Kim, Sujung; Cha, Jae Won
Abstract : Augmented reality (AR) is becoming more useful for head‐up displays (HUDs) through the advantage of realistic visual information. However, due to the lack of consistency with the environment, current HUDs do not reflect the real environment and deliver only simple information. We have developed a natural 3D AR HUD, AHEAD, through HD maps, visual localization, and 3D perspective optical technology. Accordingly, AHEAD allows the driver to effortlessly identify virtual images as if they exist in the actual driving space.